Smart Learning Environments - Tlili, Ahmed; Popescu, Elvira; Huang, Ronghuai; Kinshuk; Soloway, Elliot; Chen, Nian-Shing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Smart Learning Environments seeks academic articles on the issues related to the reform of the ways of teaching and learning through advancing current learning environments towards smart learning environments. It provides opportunities for discussions and constructive dialogue among various stakeholders on the limitations of existing learning environments, need for reform, innovative uses of emerging pedagogical approaches and technologies, and sharing and promotion of best practices, leading to the evolution, design and implementation of smart learning environments. The aim of the journal is to help various stakeholders of smart learning environments better understand each other's role in the overall process of education and how they may support each other.
Keywords: Education; Education$1 (BData processing.s; Education; Computers and Education